The intravitreal injection: variations in regulations, cost and reimbursement in Europe - Michels, Stephan; Becker, Matthias D. (Spektrum der Augenheilkunde, 2012)
SummaryBACKGROUND: Large randomized controlled clinical trials have established excellent evidence for the most frequent exudative macular diseases (neovascular age-realted macular degeneration, macular edema due to diabetes and retinal vein occlusions) how to treat with intravitreal vascular endothelial growth factor inhibitors. Due to multiple limitations such optimal, best evidence-based treatment is hardly manageable in any European country. MATERIAL AND METHODS: The subsequent overview outlines the key factors and their variability throughout Europe that limit the chance for adequate patient treatment. To outline the differences a survey was conducted among European retina specialists. Among the key limitations for optimal treatment are the drug label valid throughout the European Union (EU) for the most commonly used approved anti-VEGF drug ranibizumab. Below the EU-wide regulations are the national and partly regional restrictions for performing and reimbursing intravitreal injections. Further restrictions can be of relevance at the level of each institution performing intravitreal injections, including budget restrictions and limitations on the number of injections performed. The results of the survey indicate significant differences throughout Europe. RESULTS: Among the key differences is the time to the final national decision on reimbursement, which can take several years in some European countries. Further differences exist among many countries on who and which institutions can conduct intravitreal injections. In most countries this is dependent on the reimbursement through the health care system. Especially in eastern European countries, institutions - being officially reimbursed for intravitreal injections - are submitted to further restrictions such as limited budgets or a limited number of injections per year. Additional relevant differences exist regarding the requirements for the injection room, ranging from just a designated room to a fully equipped operating room. This has in addition to safety significant implications on cost and time-efficient patient treatment. The reimbursement for the intravitreal injection procedure at institutions with official reimbursement by the health care system varies throughout Europe from about 80 to 600 €. Unfortunately, in many countries the organizational structures and incentives have - to the disadvantage of patients and treating ophthalmologists - not yet been adopted to the needs of the era of intravitreal injections. CONCLUSIONS: With a growing number of affected and by intravitreal anti-VEGF injections treatable patients there will be an increasing pressure on improving access to adequate treatment. More uniformity regarding requirements and reimbursement throughout Europe is desirable. Unfortunately a further trend to regionalization is observed.
Gesehen am 29.11.2018